PENGEMBANGAN MODUL IPA BERBASIS STEM SDGs UNTUK MENINGKATKAN KETERAMPILAN KOMUNIKASI ILMIAH SISWA SMP - Lukito Bayu Utomo; Pramudya Dwi Aristya Putra; Firdha Yusmar (LPPM Universitas Muhammadiyah Muara Bungo, 2025)
Science is a subject that requires special skills that students must have, one of which is scientific communication skills. Scientific communication skills have not been the focus of science learning at the junior high school level, which causes many students to have low levels of scientific communication skills. The purpose of developing a STEM SDGs-based science module is to determine how effective the use of the developed module is by integrating it with STEM SDGs in improving the scientific communication skills of junior high school students. The research conducted was a development type using the ADDIE model which went through five stages, namely the analysis, design, development, application, and evaluation stages. The product was tested using two tests, namely the effectiveness test and the validity test. Learning using the STEM SDGs-based science module that was developed has passed both tests well, indicating that the STEM SDGs-based science learning module has been proven valid and effective in improving the scientific communication skills of junior high school students.